因式分解25(m+n)^2-(m-n)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 02:18:14
因式分解25(m+n)^2-(m-n)^2因式分解25(m+n)^2-(m-n)^2因式分解25(m+n)^2-(m-n)^2(5(m+n)+(m-n))*(5(m+n)-(m-n))=(6m+4n)
因式分解25(m+n)^2-(m-n)^2
因式分解25(m+n)^2-(m-n)^2
因式分解25(m+n)^2-(m-n)^2
(5(m+n)+(m-n))*(5(m+n)-(m-n))=(6m+4n)(4m+6n)
25(m+n)^2-(m-n)^2
=[5(m+n)+(m-n)][5(m+n)-(m-n)]
=(5m+5n+m-n)(5m+5n-m+n)
=(6m+4n)(4m+6n)
=4(3m+2n)(2m+3n)
16(m+n)^2+40(m+n)(m-n)+25(m-n)^2 怎样因式分解?
因式分解(m-n)^2-(m+n)^2
(m-n)(m-n+2)-8因式分解
因式分解m^2-n^+m-n
因式分解m^2-(n+1)m+n
因式分解25(m+n)^2-4(m-n)^2
因式分解25(m+n)^2-(m-n)^2
4(m-n)^2-20(n-m)+25 因式分解
(m-n)^2-10(n-m)+25 因式分解
(m+n)^2-10m-10n+25因式分解
因式分解(m-n)^2-(n-m)(m 2n)
m^2(m-n)+n^2(n-m)因式分解
因式分解(n-m)^3(m-n)^2-(m-n)^5
因式分解4m^2(m-n)+4n(n-m)
(m-n)+2n(m-n)(m-n)的平方+2n(m-n)因式分解
m^2-25n^2 因式分解
因式分解(m-n)^2-1
(m-n)*2+2n(n-m)*2的因式分解